Inflammation and clinical response to treatment in depression: A meta-analysis - Strawbridge, R.; Arnone, D.; Danese, A.; Papadopoulos, A.; Herane Vives, A.; Cleare, A.J. (European neuropsychopharmacology, 2015)
The depressive state has been characterised as one of elevated inflammation, which holds promise for better understanding treatment-resistance in affective disorders as well as for future developments in treatment stratification. Aiming to investigate alterations in the inflammatory profiles of individuals with depression as putative biomarkers for clinical response, we conducted meta-analyses examining data from 35 studies that investigated inflammation before and after treatment in depressed patients together with a measure of clinical response. There were sufficient data to analyse IL-6, TNFα and CRP. Levels of IL-6 decreased with antidepressant treatment regardless of outcome, whereas persistently elevated TNFα was associated with prospectively determined treatment resistance. Treatment non-responders tended to have higher baseline inflammation, using a composite measure of inflammatory markers. Our findings suggest that elevated levels of inflammation are contributory to treatment resistance. Combining inflammatory biomarkers might prove a useful tool to improve diagnosis and detection of treatment refractoriness, and targeting persistent inflammation in treatment-resistant depression may offer a potential target for the development of novel intervention strategies.